New situations facing the NICs in East Asia - Detlef Lorenz (Intereconomics, 1986)
The newly industrialising countries (NICs) in the East Asian region are beginning to be faced with serious problems: problems involved not only in moving from an easy phase of import substitution to a more difficult second stage, but also in progressing from the first to the second more demanding phase of export orientation. Professor Lorenz analyses this new situation.
Keywords: 330; Foreign Trade